(untitled)
Let G be a finite group. An irreducible character χ of G is said to be primitive if χ eq ϑ^G for any character ϑ of a proper subgroup of G. In this paper, we consider about the zeros of primitive characters. Denote by Irr_pri (G) the set of all irreducible primitive characters of G. We proved that if gG and the order of gG' in the factor group G/G' does not divide |Irr_pri (G)|, then there exists φ Irr_pri (G) such that φ(g)=0. , number=1, journal=Journal of Mathematical Study, year=2022, month=Mar., pages=67–70